Leveraging of Business Growth Strategies For Superior Firm Performance in the Malaysian Property Sector - Kartinah, Ayupp; Daw, Tin Hla; Mohd Razali, Mohd Waliuddin (2018)
This paper aims to highlight the importance of choosing the correct types of business growth strategies to ensure a fit with the business environment for firm’s superior performance. The Malaysian property sector was chosen due to it dynamic nature and its importance to the country’s economic growth. The scope of the study covers seventy-six property-sector firms listed under Bursa Malaysia, with 15 years of time span coverage data used. Factors that affect the dynamics of growth strategy activities were studied to see the connection with a firm’s superior financial performance. Both quantitative and qualitative data analysis were utilised, that are; the qualitative analysis for the level of growth strategy, while the panel data regression technique comprises the grouping of the time series data and cross-sectional data to examine performance and other relevant factors. The findings show that high performance firms adopt business growth strategies in the area of product development, new market and also practice risk management. Panel regression results indicate that these business growth strategies have a positive impact on the superior firm performance of the business.